2016
DOI: 10.1597/14-093.1
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Alveolar Bone Grafting (CLEFTSiS) 2007–2010

Abstract: Objective To determine whether alveolar bone graft outcomes for unilateral and bilateral cleft lip and palate patients have continued to improve since the reorganization of cleft services in Scotland in 2000. Design Retrospective analysis of postoperative anterior occlusal radiographs. Patients and Participants Eighty-one of 106 patients who were eligible for alveolar bone grafting between 2007 and 2010 had suitable postoperative radiographs available. Interventions Twenty-seven percent of the patients (n = 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 55 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…However, there is debate over the optimal timing of surgery and coordinated orthodontic treatment as well as to how to specifically define bone graft success. Authors attempted to understand from the literature the ideal timing, appropriate use of orthodontics, and methods of evaluating bone graft outcomes, but there is no well-defined consensus regarding the above questions 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is debate over the optimal timing of surgery and coordinated orthodontic treatment as well as to how to specifically define bone graft success. Authors attempted to understand from the literature the ideal timing, appropriate use of orthodontics, and methods of evaluating bone graft outcomes, but there is no well-defined consensus regarding the above questions 7 …”
Section: Discussionmentioning
confidence: 99%
“…Authors attempted to understand from the literature the ideal timing, appropriate use of orthodontics, and methods of evaluating bone graft outcomes, but there is no well-defined consensus regarding the above questions. 7 Similar systematic reviews have been performed to evaluate the optimal timing of alveolar bone grafting in patients with CLP. Kaura et al 5 performed a review of seventeen manuscripts and concluded that the success of secondary bone grafting was high, but there was considerable variation and no consensus on the use of chronological age or dental age as a marker for appropriate timing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies based only on radiographic outcomes, despite their limitations, are definitely important and very valuable in our further understanding of details of such procedures. In particular, the studies based on multicenter evaluation with longitudinal data, analyzed by experts in the field can further advance our knowledge and possibly assist us to modifying/improving some of our surgical techniques 21–25 . Such studies should be considered in isolation, as they do not encompass all of the widely accepted final goals of the procedure including dental eruption, orthodontic success, and if needed prosthodontic care leading to definitive skeletal and soft tissue functional and esthetic habilitation.…”
Section: Discussionmentioning
confidence: 99%